Resveratrol Pretreatment Inhibits Myocardial Apoptosis in Rats Following Coronary Microembolization via Inducing the PI3K/Akt/GSK-3β Signaling Cascade - Li T; Chen Z; Zhou Y; Li H; Xie J; Li L (Dove Medical Press, 2021)
Tao Li, Zhiqing Chen, You Zhou, Haoliang Li, Jian Xie, Lang Li Department of Cardiology, The First Affiliated Hospital of Guangxi Medical University & Guangxi Key Laboratory Base of Precision Medicine in Cardio-Cerebrovascular Diseases Control and Prevention & Guangxi Clinical Research Center for Cardio-Cerebrovascular Diseases, Nanning, People's Republic of ChinaCorrespondence: Lang LiDepartment of Cardiology, The First Affiliated Hospital of Guangxi Medical University & Guangxi Key Laboratory Base of Precision Medicine in Cardio-Cerebrovascular Diseases Control and Prevention & Guangxi Clinical Research Center for Cardio-Cerebrovascular Diseases, 6 Shuangyong Road, Nanning, 530021, Guangxi, People's Republic of ChinaTel/Fax +86-771-5331171Email drlilang1968@126.comPurpose: Coronary microembolization (CME) is associated with progressive cardiac dysfunction, myocardial inflammation, and apoptosis. Resveratrol (RES) has a considerable role in cardioprotection. However, the contribution and possible mechanisms of RES in CME have not been clearly understood.Methods: In the current study, 40 SD rats were randomly selected and categorized into various groups including CME, CME + resveratrol (CME + RES), CME + resveratrol+ LY294002 (CME + RES + LY), and sham groups (10 animals in each group). The inert plastic microspheres (42 μm) were injected into the rats' left ventricle for developing the CME model. Then resveratrol (25 mg/kg/d) was given to the rats in the CME + RES and CME + RES + LY groups for one week before CME induction. Furthermore, LY294002 (10 mg/kg) was intraperitoneally injected into the rats of the CME + RES + LY group 0.5 hours before CME modeling. The cardiac functions, serum levels of myocardial injury biomarkers, myocardial histopathology, and mRNA and proteins associated with myocardial apoptosis were all assessed 12 hours after surgery.Results: The results revealed that resveratrol pretreatment alleviated the CME-induced myocardial damage by improving cardiac dysfunction, and lowering the serum level of myocardial injury biomarkers, myocardial microinfarct size, and cardiomyocyte apoptotic index. Pretreatment with resveratrol reduced the level of proteins and mRNAs associated with the pro-apoptosis in myocardial tissues and increased the levels of proteins and mRNAs associated with the anti-apoptosis. Moreover, the combined treatment of resveratrol and LY294002 reversed the observed protective effects.Conclusion: Resveratrol can inhibit cardiomyocyte apoptosis, thus attenuating the CME-induced myocardial injury by triggering the PI3K/Akt/GSK-3β cascade.Keywords: resveratrol, myocardial apoptosis, PI3K/Akt/GSK-3β, coronary microembolization, cardiac dysfunction